Combined experimental and numerical study of uniaxial compression failure of hardened cement paste at micrometre length scale. (December 2019) - Zhang, Hongzhi; Xu, Yading; Gan, Yidong; Chang, Ze; Schlangen, Erik; Šavija, Branko
Abstract: The aim of this work is to investigate the mechanical performance of hardened cement paste (HCP) under compression at the micrometre length scale. In order to achieve this, both experimental and numerical approaches were applied. In the experimental part, micrometre sized HCP specimens were fabricated and subjected to uniaxial compression by a flat end tip using nanoindenter. During the test, the load-displacement curves can be obtained. In the modelling part, virtual micrometre sized specimens were created from digital material structures obtained by X-ray computed tomography. A computational compression test was then performed on these virtual specimens by a discrete lattice fracture model using the local mechanical properties calibrated in the authors' previous work. A good agreement is found between the experimental and numerical results. The approach proposed in this work forms a general framework for testing and modelling the compression behaviour of cementitious material at the micrometre length scale.